Idiopathic unilateral lower limb gangrene in a neonate - Jagjit Singh; K N Rattan; Geeta Gathwala; Yogender Singh Kadian (Wolters Kluwer Medknow Publications, 2011)
We are reporting a very unusual case of unilateral lower limb gangrene in 12 days neonate, who was brought to us with bluish discoloration of left foot with gangrene of toes. A negative sepsis screen, normal Doppler study, normal magnetic resonance angiography and absence of evidence of hypercoagulable state prompted us to make the diagnosis of idiopathic unilateral lower limb gangrene in this newborn. Because of the rarity we are reporting this case with vide review of literature.